PENINGKATAN KAPASITAS WANITA TANI DALAM MANAJEMEN INFORMASI DATA TERNAK KWT SARI MAJU DI DESA MENGWI - I Putu Eka Indrawan; Ni Nyoman Parmithi; Ni Luh Putu Yesy Anggreni; Pande Komang Suparyana (Universitas Mataram, 2023)
Management of data information in the form of administrative bookkeeping in groups is very necessary in livestock business activities. Policies in decision-making related to health and the potential economic value of livestock can be seen from records made in the books of livestock groups. The purpose of implementing this activity is to assist and improve the skills of breeders in administrative bookkeeping of livestock management activities. The activity location is in Lebah Pangkung Banjar, Mengwi Village, Badung Regency. The target partner is the Sari Maju Farmer Women's Group with a total of 15 members. The participatory rural appraisal (PRA) model is used as a method for implementing this community service activity. The level of skills during administrative management counseling activities for partners is carried out with the Pre-test and Post-test instruments. The results of the activity showed that the partner's skill level increased 100% to the category of understanding in filling out group administration. This activity also produces a book that has been prepared by partners to be used as a recording of group activities in conducting livestock business.